The non-avian theropod quadrate I - Hendrickx, Christophe (2015)
Sem PDF. This research was supported by the Fundacao para a Ciencia e a Tecnologia (FCT) scholarships (Ministerio da Ciencia, Tecnologia e Ensino superior, Portugal) SFRH/BD/62979/2009 (CH) and SFRH/BPD/96205/2013 (RA). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.